Implementasi Program Madrasah Inovasi di MAN 2 Langsa - M. Zakir (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
The innovative madrasah program is the beginning of a program that causes significant changes to take place within the establishment. For instance, the enhancement or addition of academic programs, faculty, staff, student recruitment, and all other currently existent components is an example of innovation. At MAN 2 Langsa, this program is also implemented through Adiwiyata, SRA (Child Friendly School), religious initiatives, healthy madrasas, and other venues. MAN 2 Langsa updated the curriculum to support the innovation madrasa program. Because the data acquired are in the form of words rather than statistics, the research adopts a qualitative method with case studies (case study research). The researcher himself serves as the study's instrument. By focusing on the capacity for inquiry, tracking, observation, understanding, and abstraction displayed by researchers. This study's historical context is MAN 2 Langsa because it is a prestigious madrasa that is in high demand in Langsa. Three methods were used in this study's data collection: participative observation, in-depth interviews, and documentation.